Method for preparing layered aluminum-tantalum radiation shielding composite cover
Patent Information
- Application Number
- CN202510807043.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-06-17
AI Technical Summary
应知,尽管采用热压复合,使层间具备一定的结合强度,但该结合强度远低于例如铝板本身,在对层状铝钽板坯进行例如模具成型时,会产生金属流动,即成型应1足以使例如铝板产生塑性变形,成型力有可能会使层状铝碳板层间产生离层或者完全脱开,最终使相关产品容易开裂
相应地,在初始阶段先进性快速加热,升温速度为12℃/min,当温度达到250℃~300℃后,停止升温,并保温10~30min;
Smart Images

Figure CN120480541B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a layered aluminum-tantalum radiation shield. Background Technology
[0002] Low Earth Orbit (LEO, within 2000 km of the Earth) satellite constellations can provide high-bandwidth, low-latency, and globally covered internet services, thus holding broad application prospects. SpaceX plans to launch 42,000 satellites to build Starlink by 2027. my country has planned the "Ten Thousand Stars Constellation Plan," namely the G60 (Qianfan constellation), GW, and "Honghu-3" constellation plans (approximately 38,000 satellites in total), with the G60 constellation expected to have approximately 15,000 satellites networked by 2030. Due to limited satellite frequency and orbit resources and the "first-come, first-served" principle, LEO satellite launches are accelerating and constellation sizes are becoming increasingly massive, leading to fierce competition for frequency and orbit resources. However, my country faces many challenges in LEO satellite launches and subsequent maintenance: firstly, high launch costs (approximately ¥60,000 / kg); secondly, relatively short satellite lifespans (5-8 years). Because the "low Earth Orbit radiation environment is not mild," especially in orbits above 1100 km, proton and electron radiation damage is a significant factor affecting the stable operation and lifespan of LEO satellites. Currently, passive radiation shielding is one of the common strategies for reducing radiation damage to satellites. High-Z (atomic number Z>26) materials are highly effective at shielding high-energy electrons and photons, while low-Z (Z<26) materials are better at shielding high-energy protons and produce fewer secondary neutrons after radiation. Ta and Al, as typical high- and low-Z materials, also possess advantages such as high chemical stability, strong corrosion resistance, and good processability, and are therefore widely used in satellite radiation shielding. However, the physicochemical properties of high- and low-Z materials differ greatly, and they have poor or even immiscibility, making metallurgical bonding difficult. Therefore, the fabrication of their layered monolithic structural components (referred to as "components") faces significant challenges.
[0003] For example, Chinese patent document CN118450688A discloses a high-strength, radiation-resistant aluminum-tantalum layered composite plate and its preparation method. In this patent document, aluminum, aluminum alloy, and tantalum or tantalum alloy are alternately layered and then placed in a vacuum chamber for hot-pressing composite. Aluminum is used as an intermediate layer to achieve hot-pressing composite, thereby ensuring the structural stability of the aluminum-tantalum layered composite plate. Since the resulting aluminum-tantalum layered composite plate can essentially be called a blank, when using this blank to manufacture, for example, a layered aluminum-tantalum radiation shielding composite cover, the blank needs to be shaped to produce the final shape of the layered aluminum-tantalum radiation shielding composite cover. It should be noted that although hot-pressing composite provides a certain bonding strength between the layers, this bonding strength is far lower than that of the aluminum plate itself. When the layered aluminum-tantalum blank is molded, for example, metal flow occurs, meaning the forming force is sufficient to cause plastic deformation of, for example, the aluminum plate. The forming force may cause delamination or complete separation between the layers of the layered aluminum-tantalum plate, ultimately making the related products prone to cracking. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a layered aluminum-tantalum radiation shield that is less prone to delamination between layers.
[0005] Based on embodiments of the present invention, a method for preparing a layered aluminum-tantalum radiation shield is provided, comprising the following steps: 1) Cut Al plates and Ta plates according to the design dimensions and remaining machining allowance of the pre-made composite cover to obtain Al blanks and Ta blanks; 2) The Al blank plate and Ta blank plate are formed into the design shape of the precast composite cover through a molding process to obtain the Al blank cover and the Ta blank cover; 3) Stack the Al blank cover and Ta blank cover in a predetermined order to form a stacked assembly; 4) The stacked assembly is hot-pressed using a vacuum hot-pressing composite process to obtain a composite cover blank; 5) According to the design dimensions of the pre-prepared composite cover, cut off the excess edges and corners of the composite cover blank to form the finished composite cover.
[0006] Optionally, before hot pressing, the stacked assembly is further subjected to an edge welding step to seal the interlayer gap from the edge and to leave an air extraction port. Accordingly, the interlayer gap is evacuated through the remaining evacuation port, and the evacuation port is sealed after the interlayer gap vacuum reaches a predetermined vacuum level.
[0007] Optionally, holes are distributed on the Ta blank; The holes on different Ta blanks contained in the same stacked assembly are staggered.
[0008] Optionally, the holes are arranged in a row and column matrix on the Ta blank, and the hole diameter is 0.5~4mm; The row spacing of the matrix is 6~10mm, and the column spacing is 6~10mm.
[0009] Optionally, the holes in the Ta blank can be formed by laser drilling.
[0010] The method for preparing a layered aluminum-tantalum radiation shield according to claim 1 is characterized in that the Ta blank shield is formed by room temperature molding. The Al blank cover forming method involves heating the Al blank plate to 250℃~350℃ and then molding it, and the corresponding mold is preheated to 250℃~350℃ before forming the Al blank cover.
[0011] Optionally, the surface cleaning of the Al preform is performed after the Al preform is formed; The surface cleaning of the Ta billet cover is carried out for the first time after the Ta billet plate is drilled, and for the second time after the Ta billet cover is formed. During the second cleaning, the edge of the Ta billet cover is pre-cut to make the surface roughness of the edge of the Ta billet cover reach 1.6~3.2μm.
[0012] Optionally, the Al billet has a thickness of 0.5 mm and the Ta billet has a thickness of 0.1 mm.
[0013] Optionally, the vacuum hot pressing composite process is performed inside the mold cavity.
[0014] Optionally, the target process temperature for vacuum hot pressing composite is 510℃~530℃; Accordingly, in the initial stage, rapid heating is first carried out, with a heating rate of 12℃ / min. When the temperature reaches 250℃~300℃, heating is stopped and the temperature is held for 10~30min. Then, the temperature is increased to the target process temperature at a rate of 6℃ / min, and held for a first stage for 30 minutes. Then keep it warm for another 2 to 3 hours.
[0015] Unlike existing technologies that first fabricate a layered aluminum-tantalum radiation shielding composite panel and then use this composite panel as the material to manufacture the final product, the method for preparing a layered aluminum-tantalum radiation shielding composite cover based on this invention first fabricates each structural layer of the layered aluminum-tantalum radiation shielding composite cover into predetermined Al and Ta blank covers, while leaving machining allowances. Then, the Al and Ta blank covers are stacked into a stacked assembly according to a predetermined number of layers. A composite cover blank is then produced through a vacuum hot-pressing composite process, and finally, the composite cover blank is trimmed to obtain the finished composite cover. From the perspective of cover forming alone, because the method of pre-forming each functional layer before composite formation eliminates interlayer metal flow and thus the delamination problem, the final prepared layered aluminum-tantalum radiation shielding composite cover is less prone to delamination and eliminates cracking caused by it. Attached Figure Description
[0016] Figure 1 This is a flowchart of the process for preparing the layered aluminum-tantalum radiation shield using embedded diffusion bonding in Example 3.
[0017] Figure 2 Scanning electron micrograph and surface diffusion width diagram of the aluminum-tantalum radiation-shielding layered composite interface prepared in Example 3.
[0018] Figure 3 Scanning electron microscopy image and surface diffusion width map of the embedded diffusion-bonded layered aluminum-tantalum radiation-shielding layered composite interface prepared in Example 3.
[0019] Figure 4 The appearance of the aluminum-tantalum radiation-shielding layered composite sample prepared in Example 1 after tearing and the tear strength curve.
[0020] Figure 5 The appearance of the aluminum-tantalum radiation-shielding layered composite sample prepared in Example 2 after tearing and the tear strength curve.
[0021] Figure 6 The appearance of the aluminum-tantalum radiation-shielding layered composite sample prepared in Example 3 after tearing and the tear strength curve.
[0022] Figure 7 The appearance of the aluminum-tantalum radiation-shielding layered composite sample prepared in Example 4 after tearing and the tear strength curve.
[0023] Figure 8 The appearance of the aluminum-tantalum radiation-shielding layered composite sample prepared in Example 5 after tearing and the tear strength curve. Detailed Implementation
[0024] It should be understood that, for aluminum-tantalum composite panels, the term "aluminum" does not specifically refer to pure aluminum, but includes both pure aluminum and aluminum alloys. This naming convention is the common naming convention in the field, and those skilled in the art should have a clear understanding of it.
[0025] In the embodiments of the present invention, the improvements mainly include the following aspects: Firstly, a pre-forming method is adopted for the structural layers of the layered aluminum-tantalum anti-corrosion composite cover to avoid delamination problems that occur when the composite cover is formed after the aluminum-tantalum composite plate is made.
[0026] Secondly, a pre-vacuuming method is adopted to avoid the problem of deep gas leakage when relying solely on vacuum hot pressing. It should be understood that even in simple flat panel composites, after lamination, the closer the gaps between the panels are to the center, the easier they are to lock in, leading to poor bonding quality.
[0027] Thirdly, opening holes in relatively thin Ta plates provides suitable process conditions, enabling diffusion bonding and metallurgical bonding between the plates.
[0028] The above three aspects will be described in detail below with reference to specific embodiments: In some embodiments, if the aluminum plate is made of aluminum alloy, the thickness of the aluminum plate is 2.5~4.5mm, preferably 4mm; if the aluminum plate is made of pure aluminum, the thickness of the aluminum plate is 0.3~0.7mm, preferably 0.5mm. It should be noted that aluminum alloy plates and aluminum plates can be used simultaneously; that is, there can be two types of aluminum plates. The relatively thinner aluminum plate can be located in the middle of the stacked assembly, while the relatively thicker aluminum alloy plate can be located on the outer side of the stacked assembly.
[0029] For tantalum plates, pure tantalum plates are selected, with a thickness of 0.01~0.3mm, preferably 0.1mm, and an areal density ranging from 0.3~0.69g / cm². In comparison, the thickness of the tantalum plate used is much smaller than that of the aluminum plate, for example, 0.1mm. If holes are made in the tantalum plate, the aluminum plates on both sides of the tantalum plate can undergo plastic deformation under given process conditions, allowing some aluminum material to connect to the opposite aluminum plate through the holes in the tantalum plate, thus forming a metallurgical connection.
[0030] Furthermore, the pure aluminum plate is a commercially available 1A99 type aluminum alloy with a pure aluminum content of not less than 99.9%, while the tantalum plate uses pure tantalum with a purity of not less than 99.5%. The main chemical element contents (by weight percentage) of the Al material are: Al 99.99%, Fe 0.003%, Si 0.003%, Cu 0.003%, and C 0.001%. The main chemical element contents (by weight percentage) of Ta material are as follows: Ta 99.97%, Ni 0.001%, Mn 0.001%, Al 0.001%, Si 0.001%, Ti 0.001%, Mg 0.001%, Mo 0.001%, N 0.003%, C 0.003%, O 0.01%, H 0.0002%, Nb 0.01%, O 0.01%, H 0.0002%, Nb 0.01%, W 0.002%.
[0031] Regarding the method for preparing layered aluminum-tantalum radiation shields, conventional steps will only be briefly described below, such as surface cleaning of the sheet material, as well as necessary steps in the art for manufacturing composite panels to improve the strength of interlayer bonding.
[0032] Step 1: According to the design dimensions of the pre-prepared composite cover, and with a given machining allowance, cut the Al plate and Ta plate to obtain Al blank and Ta blank for later use.
[0033] Step 2: Use sandpaper to polish the surfaces of the 0.5mm thick 1A99 aluminum alloy Al billet and the 0.1mm thick Ta billet to remove the surface oxide layer. Then, clean with acetone and ethanol for 15 minutes to remove surface oil. Air dry or dry in an oven to obtain the surface-treated 1A99 aluminum alloy Al billet and Ta billet.
[0034] Step 3: Design and manufacture a separate mold for each Al and Ta billet cover. It should be understood that, for example, the curvature of different structural layers in a sphere varies, and this should be clearly understood based on the concept of this invention. The purpose of using mold forming is to ensure that the dimensional deviations of the obtained Al and Ta billet covers are within a predetermined range by utilizing the efficiency of mold forming and the consistency of the produced products.
[0035] Furthermore, considering ductility, relatively thick Al billets are deep-drawn at temperatures between 250 and 350°C. To prevent rapid temperature loss during processing, the forming dies also need to be heated. The 250-350°C temperature range is relatively suitable, as aluminum or aluminum alloys are less prone to oxidation, and aluminum plates of the appropriate thickness and size exhibit good ductility, preventing processing defects. Since pure Ta has high ductility at room temperature, and the selected Ta plate thickness is relatively small, the Ta billet can be deep-drawn at room temperature.
[0036] Step 4: In some embodiments, blank cover flanges are formed around the periphery of the deep-drawn Al and Ta blank covers to facilitate stacking and subsequent processing. Furthermore, to reduce deformation during the trimming of the single-layer blank cover flange and improve the surface quality of the cut, laser processing is used for trimming. Laser cutting does not produce defects such as edge collapse. Finally, the surface of the single-layer blank cover is treated with the same mechanical and chemical methods as in Step 2 to remove scale and oxide layers, ensuring the quality of the vacuum hot-pressing composite.
[0037] Step 5: In some embodiments, a three-dimensional model of a tantalum billet cover with a gradient pore density distribution is established, wherein the pore distribution model includes at least two pore diameter gradient variation modes.
[0038] For composite shields, the perforation distribution on Ta plates refers to the relative positions of perforations on the same Ta plate and the relative positions of perforations on different Ta plates. A reasonable perforation distribution should first ensure that the projections of perforations on all Ta plates in the stacked assembly do not overlap in the XY plane, thereby ensuring high radiation shielding performance.
[0039] The holes drilled in the Ta billet or Ta billet cover have a diameter of 0.5~4mm and are arranged in a matrix. The row spacing in the row and column matrix of the holes is 6~10mm and the column spacing is 6~10mm.
[0040] Step 6: Import the 3D model into the laser processing system and generate a multi-axis linkage processing path. This path includes a normal vector compensation algorithm to ensure the laser beam is always perpendicular to the surface to be processed. Correspondingly, if holes are formed on the Ta blank plate before the Ta blank cover is formed, the difficulty of forming the holes is relatively low. However, after the Ta blank cover is formed, it is difficult to ensure that the holes on different Ta blank covers contained in the same stacked assembly are staggered. Under the aforementioned 3D model conditions, the 3D dimensions of the Ta blank covers contained in the same stacked assembly are already determined, thus making it easy to ensure that the holes on different Ta blank covers contained in the same stacked assembly are staggered.
[0041] Step 7: Set the baseline parameters for laser drilling: pulse energy 20~80J / cm², pulse width 10~100μs, repetition frequency 20~100kHz, and auxiliary gas (nitrogen or argon or other inert gas) pressure 0.3~0.8MPa.
[0042] Step 8: Configure a high-pressure gas-solid two-phase flow nozzle (pressure 0.6~1.2MPa, nitrogen content 85%), and use a spiral progressive purging path to clean the surface dust or debris of the billet cover by purging.
[0043] Step 9: Continue grinding and polishing the Ta billet cover after laser drilling, especially the edges of the holes and the laser-cut surfaces, to achieve a surface roughness of 1.6~3.2μm. Finally, use ultrasonic cleaning to remove oil and dust from the surface of the Ta billet cover.
[0044] Step 10: Based on the dimensions of the aluminum and tantalum billets cut in Step 1, or directly using the flange dimensions of the Al billet cover, use laser cutting to process the Al gasket used for welding the composite cover. Perform the same grinding and cleaning method as in Step 1 on the Al gasket to remove surface dirt and oxide layers, facilitating welding. The Al gasket is essentially a ring, with the ring hole size roughly equivalent to the outer edge of the flange after the Al and Ta billet covers are stretched.
[0045] Furthermore, the Al pad serves as an auxiliary material, primarily used to assist in the seam welding operation of the stacked assembly. Since aluminum and tantalum cannot be directly welded, forced welding would result in poor quality and affect the vacuum performance of the composite cover. Aluminum-aluminum welding, however, yields excellent results. Therefore, the Al pad provides an aluminum-aluminum welding interface at the edge of the stacked assembly. Additionally, when the composite cover is assembled in the sequence Al blank cover I / Ta blank cover I / Al blank cover II / Ta blank cover II / Al pad / Al blank cover III, if the sheet metal is thick, there will be a height difference between Al blank cover I and Al blank cover III. During seam welding, the upper and lower plates will undergo significant plastic deformation, affecting welding quality and vacuum performance. The Al pad can fill this height difference, making the edges smooth and facilitating seam welding. Simultaneously, the Al pad can be used to create process holes for vacuuming. These process holes are pre-drilled at predetermined locations, and the remaining portions are welded to the flange of the stacked assembly, thus facilitating vacuuming operations. After the composite blank cover is processed, the Al pad can be removed by using a laser cutting machine to cut off the seam welding edge of the composite cover, ensuring the dimensional accuracy of the composite cover.
[0046] It should be understood that the overall shape of a composite cover is generally dome-shaped or similar, and the structure is relatively simple. Therefore, the stacked assembly is easy to implement due to the structural similarity. Furthermore, the opening of a composite cover usually has a flange structure to facilitate the installation of the composite cover at the given protected location. Therefore, the Al gasket is a circular or rectangular ring structure adapted to the outer edge of the flange.
[0047] Step 11: Assemble the Al blank cover I / Ta blank cover I / Al blank cover II / Ta blank cover II / Al pad / Al blank cover III in that order to form a stacked assembly. Then, use welding equipment to perform seam welding along the edge of the stacked assembly and check the airtightness of the weld.
[0048] To check for airtightness, nitrogen gas can be introduced to 0.1 MPa through the remaining process port, avoiding excessive pressurization. After closing the inflation valve and allowing it to stand for, for example, 3 minutes, observe the pressure gauge reading on the process port connection line. If there is no pressure loss or the pressure loss is less than or equal to 0.003 MPa, it is considered leak-free.
[0049] The Al pad has a width of 5~10mm and a thickness of 2~5mm. A process hole clearance is reserved at the end of the seam weld. Vacuuming is carried out using this process hole. This vacuuming is for pre-vacuuming, rather than vacuuming in the vacuum hot pressing process equipment, which can ensure the relative thoroughness of vacuuming.
[0050] Al pads can be omitted, mainly because the Ta plates are relatively thin, and welding between Al blanks can skip the Ta blanks, allowing for direct layer-by-layer stacking to form the stacked assembly. However, using Al pads is still preferred.
[0051] Step 12: Use a vacuum pump to evacuate the process hole until the vacuum level reaches below 10 Pa, and then weld the process hole to seal it.
[0052] For the welding and sealing of process holes, hydraulic clamps can be used to compress and deform the pipe to which the process hole is adapted, forming a pleated seal (similar to the crimping of the ends of an electrical connector), thus creating the first seal. After removing the vacuum equipment, welding can be performed again at the adapted pipe to form a second seal.
[0053] After the seam welding of the stacked assembly is completed, the metal intake pipe can be welded at the reserved process hole.
[0054] Step 13: Place the vacuum-sealed and welded assembly from Step 12 onto the pre-prepared mold, specifically as follows: Figure 1 The lower mold, located on the bottom side, is placed on the stacked assembly, and then the upper mold, located on the top side, is placed on top of the stacked assembly. The mold and the stacked assembly are then placed together in a vertical vacuum hot pressing sintering furnace. The vertical vacuum hot pressing sintering furnace is then evacuated to a vacuum level of 0.1~10Pa, preferably 0.1Pa.
[0055] Step 14: After the vertical vacuum hot pressing sintering furnace reaches the required vacuum level, gradient heating heat treatment is carried out, which consists of four stages: rapid heating, slow heating, heat penetration and diffusion bonding.
[0056] The process begins with a rapid heating phase at a rate of 12°C / min. Once the temperature reaches 250-300°C, heating is stopped and maintained for 10-30 minutes to ensure uniform heating of the stacked assembly. A slow heating phase follows, with a heating rate of 6°C / min. The heat penetration phase lasts for 30 minutes. In the diffusion bonding phase, the composite panels undergo diffusion bonding at a working temperature of 510-530°C and a holding time of 2-3 hours. Throughout the hot-pressing process, a pressure of 3-5 MPa is maintained.
[0057] Step 15: Cooling stage. The stacked assembly is cooled to room temperature with the furnace. The vertical vacuum hot pressing sintering furnace is opened, the mold is removed, and the composite cover blank of the aluminum-tantalum radiation shield is taken out.
[0058] Step 16: The cooled composite cover blank is trimmed by CNC milling to remove 0.5~1.2mm of excess material around the perimeter, and the roughness Ra of the trimmed edge is controlled to be ≤3.2μm to obtain the final product, namely the composite cover finished product.
[0059] At the same time, if an Al pad is present, the Al pad will inevitably be removed when the corresponding excess is removed.
[0060] The following description uses an aluminum billet and a tantalum billet with a Ta plate thickness of 0.1 mm and an Al plate thickness of 0.5 mm, after the surfaces to be welded have been cleaned. The example is based on the aforementioned 16 steps, with adjustments made to the main process parameters, and the rest is the same as above. Example
[0061] according to Figure 1 The arrangement shown is Al shield I / Ta shield I / Al shield II / Ta shield II / Al pad / Al shield III.
[0062] The working temperature in step 14 is 510℃, corresponding to a working pressure of 3MPa, and the holding time is 2 hours. The aluminum-tantalum composite cover prepared in Example 1 was made into a tear test specimen and subjected to a tear test in a CMT5305-300kN microcomputer-controlled electronic universal testing machine. Figure 4 This is the result of tearing the sample from Example 1. As can be seen from the peeled sample image, the interface of the aluminum-tantalum composite cover produced at 510℃ for 2 hours after peeling is relatively smooth. There is no Al / Al welding between the two aluminum plates through the voids in the tantalum plate. From the peel strength... Figure 4 As can be seen, the tear curve presents a plateau region composed of a large number of straight lines, with a very small load and a maximum peel strength of only 0.0098 kN / mm, indicating that a reliable connection has not been achieved at this point. Example
[0063] according to Figure 1The arrangement shown is Al shield I / Ta shield I / Al shield II / Ta shield II / Al pad / Al shield III.
[0064] The working temperature in step 14 is 510℃, corresponding to a working pressure of 3MPa, and the holding time is 2.5h. The aluminum-tantalum composite cover prepared in Example 2 was made into tear test specimens and subjected to tear tests using a CMT5305-300kN microcomputer-controlled electronic universal testing machine. Figure 5 The image shows the results of tearing the aluminum-tantalum composite cover sample prepared in Example 2. When the heat treatment time is 2.5 hours, the interface after peeling is still relatively smooth. However, clear hole imprints are visible on the aluminum plate, indicating slight welding between the two aluminum layers. The heat treatment time was insufficient, and the welding effect was not significant. The peel strength diagram shows that when peeling to the void, the peel strength reaches a maximum of 0.09 kN / mm due to the welding between the two aluminum layers. Example
[0065] according to Figure 1 The arrangement shown is as follows: Al shield I / Ta shield I / Al shield II / Ta shield II / Al pad / Al shield III.
[0066] The working temperature in step 14 is 510℃, corresponding to a working pressure of 3MPa, and the holding time is 3h. The aluminum-tantalum composite cover prepared in Example 3 was made into tear test specimens and subjected to tear tests using a CMT5305-300kN microcomputer-controlled electronic universal testing machine. Figure 6 The image shows the results of tearing the aluminum-tantalum composite cover sample prepared in Example 3. As the holding time increased to 3 hours, compared to 2 hours and 2.5 hours, it was clearly visible in the peeled sample image that, due to the full welding of Al cover I and Al cover II, the hole imprints on Al cover II became clearer, while Al cover I was left with corresponding voids. Simultaneously, the surface roughness of both Al and Ta plates increased. The peel strength curve showed a cyclical trend of first increasing, then decreasing, then increasing again and decreasing once more. This is because as the peeling experiment continued, the peel strength decreased after peeling through the hole, and then increased again when reaching the next location to drill a hole in the Ta plate. The maximum peel strength after 3 hours of holding time reached 0.174 kN / mm. Example
[0067] according to Figure 1 The arrangement shown is Al shield I / Ta shield I / Al shield II / Ta shield II / Al pad / Al shield III.
[0068] The working temperature in step 14 is 520℃, corresponding to a working pressure of 3MPa, and the holding time is 3h. The aluminum-tantalum composite cover prepared in Example 4 was made into tear test specimens and subjected to tear tests using a CMT5305-300kN microcomputer-controlled electronic universal testing machine. Figure 7 The image shows the tear test results of the aluminum-tantalum composite cover obtained in Example 4. At 520°C, it was observed that as the temperature increased, aluminum precipitation from the aluminum plate became more severe, the thickness of the composite plate gradually decreased, and the bonding strength at the pores was high. The peel strength curve of the 510°C / 3h sample also showed a cyclical trend of first increasing, then decreasing, then increasing again and decreasing again. However, the maximum peel strength decreased to 0.075 kN / mm due to the overall thinning of the aluminum-tantalum composite cover. Example
[0069] according to Figure 1 The arrangement shown is Al shield I / Ta shield I / Al shield II / Ta shield II / Al pad / Al shield III.
[0070] The working temperature in step 14 is 530℃, corresponding to a working pressure of 3MPa, and the holding time is 3h. The aluminum-tantalum composite cover prepared in Example 5 was made into tear test specimens and subjected to tear tests using a CMT5305-300kN microcomputer-controlled electronic universal testing machine. Figure 8 The results of tearing the aluminum-tantalum composite cover finished product sample in Example 5 are shown. At 530°C, it was observed that during the peeling process, aluminum precipitation from the aluminum plate was also quite severe, and the overall thickness of the finished aluminum-tantalum composite cover gradually decreased. At the same time, the bonding strength at the holes was high, resulting in the phenomenon that the middle hole could not be peeled off, thus reducing the maximum peel strength to 0.027 kN / mm.
[0071] Additionally, regarding the row and column spacing of the holes on the tantalum plate, choosing a 6mm row and column spacing has the following advantages: [1] The smaller spacing (6mm) means that the holes on the tantalum plate are more densely distributed. The dense hole structure can increase the contact area between aluminum and tantalum, forming more bonding points through vacuum diffusion welding, which may improve the interfacial bonding strength and reduce the risk of delamination.
[0072] [2] Tantalum plates have a higher porosity and are lighter overall, making them suitable for aerospace applications with strict weight reduction requirements. The coefficients of linear expansion of aluminum and tantalum differ significantly, and the dense hole structure can alleviate stress concentration caused by thermal deformation.
[0073] shortcoming: [1] A decrease in the proportion of solid tantalum may lead to a decrease in the overall tensile strength and yield strength of the composite material (due to the reduction in the load-bearing area of tantalum). [2] A 6mm spacing will weaken the continuity of the tantalum layer, which may reduce the radiation shielding effectiveness (especially the blocking of high-energy particles or X-rays). [3] The processing is difficult and the dense hole structure requires higher requirements for the laser drilling process of tantalum plates, which may increase the manufacturing cost.
[0074] Choosing an 8mm row and column spacing has the following advantages: [1] An 8mm pitch is a balanced choice, with a moderate proportion of solid area in the tantalum plate, which can maintain high tensile strength while reducing weight through the hole structure.
[0075] [2] The aluminum-tantalum bonding surface is formed by diffusion welding to form a uniform connection, resulting in a more uniform stress distribution and avoiding local stress concentration.
[0076] [3] The tantalum layer has good continuity and can form an effective composite shielding structure when combined with the aluminum layer. The process is stable: the drilling / laser processing difficulty is moderate, making it suitable for mass production.
[0077] shortcoming: [1] Compared with a 6 mm pitch, the amount of tantalum used is increased, but it is still significantly better than the pure tantalum structure.
[0078] [2] Its adaptability to extreme environments is limited, and further optimization may be needed under ultra-high radiation or ultra-strong loads.
[0079] Choosing a 10mm row and column spacing has the following advantages: [1] The larger row and column spacing results in a higher proportion of solid area in the tantalum plate, which significantly improves the tensile strength and stiffness of the composite material.
[0080] [2] Tantalum layer has the best continuity, radiation shielding effectiveness close to that of pure tantalum plate (especially for high-energy radiation), better impact resistance, and tantalum toughness can effectively resist impacts from micrometeorites or space debris.
[0081] shortcoming: [1] The reduced contact area between aluminum and tantalum may decrease the interfacial bonding strength, requiring strict optimization of the diffusion welding process (such as temperature / pressure). [2] The weight increased significantly due to the large amount of tantalum used, which offset the lightweight advantage of aluminum.
[0082] [3] The cost is high. Tantalum is expensive and excessive use will significantly increase manufacturing costs.
[0083] Regarding the hole diameter in tantalum plates, choosing a small hole diameter of 0.5mm has the following advantages: [1] The pore density can be made higher, which can theoretically maximize the actual effective bonding area, and help to significantly improve the interlaminar shear strength and anti-delamination ability. The dense interlocking structure of small pores can more effectively transfer stress and reduce stress concentration at the interface. [2] It minimizes the weakening of the tantalum substrate and has a relatively weak stress concentration effect at the hole edge. This is beneficial for maintaining the continuity and structural integrity of the tantalum plate as a functional layer (radiation protection).
[0084] shortcoming: [1] It has the greatest processing difficulty and requires extremely high precision in laser perforation. [2] The resistance of aluminum material flowing into the micropore is relatively large (sufficient pressure / temperature / time is required to ensure the filling rate). The risk of insufficient filling is high, which may result in unfilled holes or poor bonding inside the holes, affecting the strength of individual interlocking points.
[0085] Advantages of choosing a medium aperture of 2mm: [1] A good balance is achieved between processing difficulty, aluminum material flowability, and the number of interlocking points. The aperture is large enough to allow the aluminum material to flow relatively easily to fill the pores under diffusion welding conditions, forming an effective mechanical anchor. At the same time, the pore density can still be maintained at a reasonable level, providing sufficient bonding points. It is expected to obtain near-optimal bonding strength, with a wide process window and good stability.
[0086] [2] Under the set diffusion welding process parameters (510-520℃, 4.5-5MPa, 2.75-3h), aluminum material has good fluidity, sufficient and reliable filling, and good process stability.
[0087] shortcoming: [1] Compared to a small aperture of 0.5 mm, the number of interlocking points per unit area is reduced. [2] It weakens the strength of the tantalum plate to a certain extent, and the stress concentration effect at the hole edge begins to appear. Advantages of choosing a 4mm large aperture: [1] It is the easiest to process, and the aluminum material has the least flow resistance, making it easy to completely fill the holes and form a single rivet with high strength. [2] It is the easiest to fill and can ensure full filling even under relatively relaxed process conditions. The quality (filling degree) of a single interlocking point is the most guaranteed.
[0088] shortcoming: The reduction in tantalum plate strength is greatest. Stress concentration at the hole edges is significant. Large holes can become weak points in the tantalum plate layer, affecting the overall stiffness and strength of the composite plate. This also reduces the continuity and protective effectiveness of the tantalum plate as a functional layer.
[0089] Regarding aperture, it usually refers specifically to diameter.
Claims
1. A method for preparing a layered aluminum-tantalum radiation shield, characterized in that, Includes the following steps: 1) Cut Al plates and Ta plates according to the design dimensions and remaining machining allowance of the pre-made composite cover to obtain Al blanks and Ta blanks; 2) The Al blank and Ta blank are formed into the designed shape of the pre-prepared composite cover through a molding process to obtain the Al blank cover and the Ta blank cover; 3) Stack the Al blank cover and Ta blank cover in a predetermined order to form a stacked assembly; 4) The stacked assembly is hot-pressed using a vacuum hot-pressing composite process to obtain a composite cover blank; 5) According to the design dimensions of the pre-prepared composite cover, cut off the excess edges and corners of the composite cover blank to form the finished composite cover; Before hot pressing, the stacked assembly is edge welded to seal the interlayer gap from the edge and leave an air extraction port. Accordingly, the interlayer gap is evacuated through the reserved evacuation port, and the evacuation port is sealed after the vacuum degree in the interlayer gap reaches the predetermined vacuum degree.
2. The method for preparing a layered aluminum-tantalum radiation shield according to claim 1, characterized in that, The Ta blank has holes distributed on it; The holes on different Ta blanks contained in the same stacked assembly are staggered.
3. The method for preparing a layered aluminum-tantalum radiation shield according to claim 2, characterized in that, The holes are distributed in a row and column matrix on the Ta blank, and the hole diameter is 0.5~4mm; The row spacing of the matrix is 6~10mm, and the column spacing is 6~10mm.
4. The method for preparing a layered aluminum-tantalum radiation shield according to claim 2, characterized in that, The holes on the Ta blank are formed by laser drilling.
5. The method for preparing a layered aluminum-tantalum radiation shield according to claim 1, characterized in that, The Ta blank forming method is room temperature molding; The Al blank cover forming method involves heating the Al blank plate to 250℃~350℃ and then molding it, and the corresponding mold is preheated to 250℃~350℃ before forming the Al blank cover.
6. The method for preparing a layered aluminum-tantalum radiation shield according to claim 1, characterized in that, Surface cleaning of the Al preform is performed after the Al preform is formed; The surface cleaning of the Ta billet cover is carried out for the first time after the Ta billet plate is drilled, and for the second time after the Ta billet cover is formed. During the second cleaning, the edge of the Ta billet cover is pre-cut to make the surface roughness of the edge of the Ta billet cover reach 1.6~3.2μm.
7. The method for preparing a layered aluminum-tantalum radiation shield according to claim 1, characterized in that, The thickness of the Al billet is 0.5 mm, and the thickness of the Ta billet is 0.1 mm.
8. The method for preparing a layered aluminum-tantalum radiation shield according to claim 1, characterized in that, The vacuum hot pressing composite process is carried out inside the mold cavity.
9. The method for preparing a layered aluminum-tantalum radiation shield according to claim 8, characterized in that, The target process temperature for vacuum hot pressing composite is 510℃~530℃; Accordingly, rapid heating is performed in the initial stage at a rate of 12℃ / min. When the temperature reaches 250℃~300℃, the heating is stopped and the temperature is maintained for 10~30min. Then, the temperature is increased to the target process temperature at a rate of 6℃ / min, and held for a first stage for 30 minutes. Then keep it warm for another 2 to 3 hours.
Citation Information
Patent Citations
High-strength and electron-radiation-resistant aluminum-tantalum layered composite board and preparation method thereof
CN118450688A
Aluminum-tantalum composite board and preparation method thereof
CN117465079A
Preform manufacturing method and composite material manufacturing method using preform
WO2020091135A1